MLA handbook for writers of research papers - Gibaldi, Joseph 1942-; Modern Language Association of America (New York Modern Language Association of America, 2003)
The revisions in the sixth edition of the MLA Handbook focus on the areas of greatest concern to students undertaking research projects today. Besides fresh citation examples, updated lists of reference works, and an improved typographic design, the new edition offers the following changes: A chapter on plagiarism explains what this offense is, why it should be taken seriously, and how good research practices prevent unintentional plagiarizing. Two dozen new annotated illustrations demonstrate how actual print and electronic sources are treated in research and documentation. Expanded, updated guidelines clarify the use and citation of online materials, including articles from subscription databases like EBSCO. The MLA documentation formats have not been changed in the sixth edition, but many guidelines have been added or refined.
Research and writing -- Plagiarism -- The mechanics of writing -- The format of the research paper -- Documentation: preparing the list of works cited -- Documentation: citing sources in the text -- Abbreviations -- Appendixes: Selected reference works by field; Other systems of documentation.
Includes bibliographical references and index.
Keywords: Report writing -- Handbooks, manuals, etc; Research -- Handbooks, manuals, etc; Bibliography -- Handbooks, manuals, etc; Abbreviations -- Handbooks, manuals, etc; Printing -- Style manuals; Research; Writing -- standards; Plagiarism; Handbooks